Psychological well being toward adolescents in disaster-prone areas in Padang city - Patricia, Helena; Rahmatiqa, Chamy; Apriyeni, Emira (International Journal Of Community Medicine And Public Health, 2020)
Background: Indonesia, particularly Padang City, West Sumatra, is a prone-area toward natural disasters related to geographical, geological and demographic conditions. Natural disasters give a very significant impact on physical, psychological and social. The psychological impact that most often appears in disaster cases is Post Traumatic Stress Disorder (PTSD). One who is prone to experiencing PTSD is adolescents. To prevent PTSD from occurring, good psychological well-being is needed. The factors that influence psychological well-being are religiosity, personality, coping strategies, self-concept and social support. Methods: This study is an analytical study with a cross sectional approach. This research was conducted in three disaster-prone districts in Padang City, namely North Padang, South Padang, and Koto Tangah. Data were collected through distributing questionnaires to 156 adolescents who were selected by purposive sampling. Data were collected by questionnaire and analyzed descriptively using univariate analysis, bivariate analysis with chi square test, and multivariate logistic regression analysis. Results: The results of this study found that 85 respondents (54.5%) had low psychological well-being, 98 respondents (62.8%) had low religiosity, 108 respondents (69.2%) had introverted personality types, 105 respondents (67.3%) used emotional focused coping, 90 respondents (57.7%) had negative self-concept and 91 respondents (58.3%) had low family support. The results of the bivariate analysis found a relationship between religiosity (0.000), personality type (0.010), coping strategy (0.00), self-concept (0.035) and family support (0.04) toward psychological well-being. Conclusions: The results of the final multivariate modeling found that adolescents with negative self-concept had 12 times chance of having low psychological well-being in disaster-prone areas in Padang City.